THE EFFECT OF MORPHOLOGICAL CHANGES IN THE BATANGHARI RIVER SIDE AREA IN PASAR, JAMBI CITY - Setyawan, Denny Iwan (Jurusan Arsitektur UPR, 2025)
Jambi City departs from civilization of the settlements along the banks of Batanghari River, since ancient Malay. The long history shows the importance of this riverside area. During the colonial period the modern city was built which is now the old city area with a part known as Pasar area. Morphologically, this early city can be seen as a complete smalltown formation. The rapid development of the city in the era of independence left traces of significant morphological changes. From a pattern that supports the basis of economic life on the control of river trade routes, it becomes oriented to the mainland. How influence of changes in the morphology of the riverbank area on the dynamics of the area is a problem that interesting to research. So with a qualitative descriptive approach, the study is directed to find a series of morphological changes that affect life of the area. It was found that there were omissions, additions or transformations of important functions in the area that changed orientation and balance of area. The loss of function of the port is the first factor that has a major impact on the region. Likewise, changes to the open space of Wilhemina Park and the implementation of a closed area parking system have made the Pasar area isolated from urban macro circulation, which previously actually supported the area.